Extending the Ukulima True Pesticide Risk Reduction Campaign in Kenya by Involving Community Health Promoters to Enhance Reach and One Health Outcomes - On Ki Li; Fredrick Mbugua; Geoffrey Rugaita; Maureen Njenga; Lynnette Echesa; Musah Samuel Matika; Hannah Odur Chore; Elizabeth Kiptoo; John Mugwanja; Hillary Korir; Fredrick Muchiri; Velma Nasimiyu; et al. (One Health Cases, 2026)
Abstract In 2023, a 6-month pilot of the Ukulima True campaign in Kenya promoted the safe use of pesticides among smallholder farmers in Subukia ward of Subukia sub-county via lead farmers, community leaders, agricultural extension officers, and media outreach. The project steering group involved county representatives from the Nakuru Food Safety Committee (FSC), including the County Department of Agriculture (DoA), the Agriculture and Food Authority (AFA), the Department of Public Health (DoH) – Community Health Services, the Pest Control Products Board (PCPB), and the Kenya Plant Health Inspectorate Service (KEPHIS). A business member organization, aak-GROW, also participated. Following a joint decision with the FSC, the campaign was extended to leverage the DoH’s network of Community Health Promoters (CHPs) in the Kabazi, Subukia, and Waseges wards. In 2024, 60 CHPs participated, reaching 100 households through their routine quarterly visits. The CHPs communicated the programme’s three key pesticide risk reduction messages using a public health framing and co-created solutions with farmers. The approach extended the reach of the campaign and led to increased safe storage of pesticide containers away from the main dwelling; increased safe disposal of used pesticide containers; reduced dumping near rivers to protect ecosystems and livestock; farmers using a red ribbon system to mark sprayed crops and respect pre-harvest intervals; and women stopping spraying pesticide during pregnancy. These positive results inspired the County DoA to sensitize a further 62 CHPs in 2025, bringing the total reach of the CHP component of the campaign to approximately 12,200 households across 2024 and 2025. Information © The Authors 2026